Transforming Physics Education in Boarding Schools: Development of STEM-Q-Based E-Modules to Improve Science Literacy - Prihatiningtyas, Suci; Shofiyah, Noly; Yunus, Sitti Rahma; Ma’arif, Iin Baroroh; Putra, Ino Angga; Haryono, Heny Ekawati (Universitas Negeri Semarang, 2025)
Digital transformation in education is a key effort by the Indonesian government to enhance the quality of national education. This study aims to develop and implement a STEM-Q (Science, Technology, Engineering, Mathematics, and Qur'an) e-Module as an innovative solution to improve science literacy in Islamic boarding schools (pesantren) The e-Module integrates scientific concepts with Qur'anic values, providing students with a contextual and relevant learning experience. The research employs a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate). Data analysis techniques involve media validity/feasibility tests using quantitative (Likert scale) and qualitative analyses based on expert assessments, calculated by percentage. A practicality test was conducted through student response questionnaires, which were analyzed with quantitative descriptive methods to evaluate material, benefits, and media suitability. An implementation test with a one-group pretest-posttest design was analyzed using descriptive statistics and the N-Gain test. Evaluation procedures include expert validation, practicality testing, and analysis of science literacy outcomes using pretest and posttest data. Expert validation results indicate that the e-module is highly quality regarding content, usefulness, ease of use, and media suitability. Practicality tests show positive reception in the field, varying scores across participating schools. Data analysis showed a significant increase in students' science literacy after applying the electronic module, with an N-Gain value in the medium category. Developing and implementing the STEM-Q e-module effectively enhances science literacy in pesantren-based schools.